Simulation and performance analysis of a cooling energy storage system based on encapsulated nano-enhanced phase change materials - Ghojavand, Fateme; Baniasadi, Ehsan; Afshari, Ebraim; Genceli, Hadi (WILEY, 2023)
The present study investigates the effects of different parameters on the performance of a cold energy storage system based on spherical capsules using two- and three-dimensional (2D and 3D) numerical analyses. The effect of different arrangements of the capsules is studied using a 2D model. The impact of using nanoparticles, diameter, and material of a spherical capsule and working parameters that affect the melting and solidification process are evaluated in a 3D model. The results revealed that the hexagonal arrangement compared to the triangular and rectangular arrangements, yields a lower charging time of 10.71% and 16.67%, respectively. Utilization of a 3% volume fraction of graphene nanoparticles in the phase change material reduces the charging and discharging process time by 11.11% and 22.22%, respectively. The diameter of the capsule is an effective parameter for the charging and discharging time, so the capsule with a diameter of 20 mm in comparison with a diameter of 40 mm reduces the charging and discharging time by 71.1% and 66.67%, respectively. Also, capsules made of graphite yield lower charging process time compared to plastic and glass capsules by 17.39% and 5%, respectively.
Keywords: cold energy storage system; nanoparticles; numerical simulation; PCM; spherical capsule; SOLIDIFICATION; RECOVERY; Energy & Fuels